Factors Related to the Motivation of Healthcare Workers in Public Health Center - Venia Oktafiani; Suci Dwi Yanti; Isna Humaera (LPPM ISTEK 'Aisyiyah Kendari, 2023)
Motivation plays a critical role in the performance, job satisfaction, and overall well-being of health workers. Understanding the factors that influence their motivation is essential for creating a supportive work environment and enhancing the quality of care provided. This is a cross sectional study consisted of 30 health profesionals who work at public health center of Kendari, Southeast Sulawesi in 2019. The results showed that all respondents were female and mostly aged 31-41 years (63.3%). Bivariat analysis showed that there was a significant relationship between high education and recent length of service towards high motivation of health workers with the p value of 0.029 and 0.024, respectovely. After multivariat analysis, the OR (95% confidence interval) of these variables were 8.94 (1.11:71.89) and 9.38 (1.29:68.23), respectively. To conclude, eduction and length of service may contribute to the motivation of health professionals. Implementing strategies that promote continuing education opportunities, professional development programs, and career advancement prospects can contribute to enhancing the motivation levels of healthcare professionals.